BENEATH the smoke of the sugar-mill : Javanese coastal communities during the tweentieth century / editor, Hiroyoshi Kano, Frans Husken, Djoko Suryo - KANO, Hiroyoshi; FRANS HUSKEN; DJOKO SURYO (Gadjah Mada University Press, 2001)
xii, 313 hlm. : ilus. ; 21 cm.